Creative tourism destination competitiveness: An integrative model and agenda for future research - Dias, Á.; Gonzalez-Rodriguez, M. R.; Patuleia, M. (Creative Industries Journal, 2023)
Creative tourism has been approached from several points of view: products and processes, enabling elements, marketing, sustainability, etc. However, to our best knowledge, there is no integrative model that brings together all its dimensions and enables a 'bird’s eye' perspective of creative destination competitiveness. As such, this article aims to present a competitiveness model for a creative tourism destination. The model presents four essential dimensions: core elements (products and processes, travelers and entrepreneurs), enablers (community engagement, stakeholders competences, and creative atmosphere), and developers (marketing and communication). Avenues for future research are presented based on the identification of areas to expand existing knowledge on creative tourism research, mainly by proposing measurement instruments which may contribute to operationalize the proposed model.